Depressive disorder in patients attending the outpatient department of a tertiary care hospital in Colombo - Anandakumar, D.; Ratnatunga, S.S.; Dayabandara, M.; Hanwella, Raveen; De Silva, V.A. (Ceylon Medical Journal, 2016)
Introduction: Lifetime prevalence of depression varies across countries and different populations. Depression is a common comorbidity of physical illness. Patients with depression are known to present with somatic symptoms. Depression is under-diagnosed in primary care settings. Objectives: To estimate the prevalence of depression in patients attending the outpatient department (OPD) of a tertiary care hospital in the Western Province of Sri Lanka. Methods: A cross-sectional descriptive study was conducted in the OPD of the National Hospital of Sri Lanka (NHSL). Sample size was 205. Every fifth patient aged between 18 and 60 years who attended the OPD was recruited until the required number was met. Centre for Epidemiologic Studies Depression Scale (CES-D) was used to identify depression. Results There were 114 (55.6%) females. Mean age was 50 years (SD 13.68). Overall prevalence of depression in the sample was 22.4%(95% CI 16.68-28.20). Prevalence of depression was higher among females 25.4%(95% CI 17.32-33.56) than in males 18.7%(95% CI 10.52-26.84). Prevalence of severe depression was 15.1%(95% CI 10.18-20.07). Adjusted odds ratios showed that pain related presenting complaints were significantly associated with depression [adjusted OR 1.99 (95% CI 1.01-3.96)]. Conclusions: Prevalence of depression in outpatients is similar to that reported in other parts of the world. None of the patients with depression presented seeking help for depressive symptoms.
Keywords: depression; hospital out-patients; Sri Lanka